2019
DOI: 10.1530/eje-18-0878
|View full text |Cite
|
Sign up to set email alerts
|

X chromosome gene dosage as a determinant of congenital malformations and of age-related comorbidity risk in patients with Turner syndrome, from childhood to early adulthood

Abstract: Objective Turner Syndrome is associated with several phenotypic conditions associated with a higher risk of subsequent comorbidity. We aimed to evaluate the prevalence of congenital malformations and the occurrence of age-related comorbid conditions and to determine whether the frequencies of congenital and acquired conditions depend on X chromosome gene dosage, as a function of karyotype subgroup. Design and methods This national retrospective observational cohort study includes 1501 patients. We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
2
19
0
1
Order By: Relevance
“…In a recent French study, including 1501 patients with TS, the median age at diagnosis was 9.4 years [5] In Europe, the Danish cytogenetic register identified all cases (n= 781) of TS alive in Denmark, during the period from 1970 to 2001. Their median age at diagnosis was 15.1 years.…”
Section: Epidemiology and Karyotypingmentioning
confidence: 99%
“…In a recent French study, including 1501 patients with TS, the median age at diagnosis was 9.4 years [5] In Europe, the Danish cytogenetic register identified all cases (n= 781) of TS alive in Denmark, during the period from 1970 to 2001. Their median age at diagnosis was 15.1 years.…”
Section: Epidemiology and Karyotypingmentioning
confidence: 99%
“…In the general population, its prevalence is 2-3% in males and 0.05% in females (4). It has been reported that the prevalence of BAV and other congenital cardiovascular malformations are more frequent in patients with a homogenous 45,X karyotype than in patients with 45,X/46,XX mosaicism (1,5). BAV is associated with proximal aortic dilatation (AD) and is a predisposing risk factor for subsequent aortic dissection (2).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in next generation sequencing have allowed for increased sensitivity to detect mosaic variants and additional studies are necessary to fully assess mosaicism as a contributor to CHD. Cytogenetic studies have demonstrated that individuals with mosaic trisomies can have CHD without associated syndromic features (Fiot et al, ; Yokoyama, Narahara, Kamada, Tsuji, & Seino, ). The Leipzig heart collection was used to study mosaicism in cardiac tissue from patients with CHD.…”
Section: Mosaicism and Chdmentioning
confidence: 99%
“…Cytogenetic studies have demonstrated that individuals with mosaic trisomies can have CHD without associated syndromic features (Fiot et al, 2019;Yokoyama, Narahara, Kamada, Tsuji, & Seino, 1992). The…”
Section: Mosaicism and Chdmentioning
confidence: 99%